Ocular manifestations in a family with brachio-oculo-facial syndrome - Rosanna Martens (2020)
© 2019 American Association for Pediatric Ophthalmology and Strabismus We report 3 siblings with brachio-oculo-facial syndrome (BOFS) who present with the predominant ocular phenotype. This syndrome has rarely been reported in multiple first-degree relatives.